The association between ambient fine particulate matter and incident adenocarcinoma subtype of lung cancer - Gharibvand, Lida; Lawrence Beeson, W.; Shavlik, David; Knutsen, Raymond; Ghamsary, Mark; Soret, Samuel; Knutsen, Synnove F. (Environmental health, 2017)
Adenocarcinoma (AC) is the most common lung cancer among non-smokers, but few studies have assessed the effect of PM on AC among never smokers. The purpose of this study was to assess the association between ambient PM and incident lung AC in the Adventist Health and Smog Study-2 (AHSMOG-2), a cohort of 80,044 non-smokers (81% never smokers) followed for 7.5 years (597,177 person-years) (2002-2011). Incident lung AC was identified through linkage with U.S. state cancer registries. Ambient PM levels at subjects' residences were estimated for the years 2000 and 2001, immediately prior to study start. A total of 164 incident lung AC occurred during follow-up. Each 10 μg/m increment in PM was associated with an increase in the hazard rate of lung AC [HR = 1.31 (95% confidence interval (CI) 0.87-1.97)] in the single-pollutant model. Excluding those with prevalent non-melanoma skin cancer (NMSC) strengthened the association with lung AC (HR = 1.62 (95% CI, 1.11-2.36) for each 10 μg/m PM increment. Also, limiting the analyses to subjects who spent more than 1 h/day outdoors, increased the estimate (HR = 1.55, 95% CI: 1.05, 2.30). Increased risk of AC was observed for each 10 μg/m increment in ambient PM concentrations. The risk was higher among those without prevalent NMSC and those who spent more than 1 h/day outdoors.